Desain Pengabdian Pembinaan Mudabbir-Mudabbirah dalam Pengasuhan Santri dengan Pendekatan Mau’idhah Hasanah pada Dayah Boarding School - Salma Hayati; Lailatussaadah; Mujiburrahman; Yusriman; Amiratun Nisak; Nargis An-Nazary (Jurnal Riset dan Pengabdian Masyarakat, 2023)
The purpose of this service-based research is to design the mentoring of mudabbir-mudabbirah in the care of santri with a mau'idhah hasanah approach in dayah of boarding school. The research method used is research and development based on Sugiyono which refers to the theory of Borg and Gall and takes three (3) steps; potential and problems, data collection and activity design. The data were analyzed in a qualitative descriptive. The results of the service-based research of mudabbir mudabbirah mentoring in nurturing santri with mau'idhah hasanah were carried out using a five-stage frame of reference; input, activities, output, purpose and goal.